2022
DOI: 10.1210/clinem/dgac643
|View full text |Cite
|
Sign up to set email alerts
|

ACROBAT Edge: Safety and Efficacy of Switching Injected SRLs to Oral Paltusotine in Patients With Acromegaly

Abstract: Context Paltusotine is a once-daily, oral, non-peptide small-molecule somatostatin receptor type 2 (SST2) agonist in clinical development for treatment of acromegaly. Objective To evaluate change in IGF-I levels in patients switched from octreotide LAR or lanreotide depot monotherapy to paltusotine. Design Phase 2, open-label, prospective, multicenter, multin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
9
0
2
Order By: Relevance
“…These examples of pharmacodynamic efficacy were mirrored in a Phase 1 clinical study in healthy volunteers, in which paltusotine acutely suppressed GHRH-stimulated GH secretion and lowered IGF-1 levels over the course of several days . In a Phase 2 study, paltusotine was shown to maintain IGF-1 levels in acromegaly patients that switched from their parentally administered depots to oral paltusotine . Currently, paltusotine is being evaluated in Phase 3 trials in acromegaly patients and a Phase 2 study in NETs patients with carcinoid syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These examples of pharmacodynamic efficacy were mirrored in a Phase 1 clinical study in healthy volunteers, in which paltusotine acutely suppressed GHRH-stimulated GH secretion and lowered IGF-1 levels over the course of several days . In a Phase 2 study, paltusotine was shown to maintain IGF-1 levels in acromegaly patients that switched from their parentally administered depots to oral paltusotine . Currently, paltusotine is being evaluated in Phase 3 trials in acromegaly patients and a Phase 2 study in NETs patients with carcinoid syndrome.…”
Section: Discussionmentioning
confidence: 99%
“… 23 In a Phase 2 study, paltusotine was shown to maintain IGF-1 levels in acromegaly patients that switched from their parentally administered depots to oral paltusotine. 30 Currently, paltusotine is being evaluated in Phase 3 trials in acromegaly patients and a Phase 2 study in NETs patients with carcinoid syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The psychometric properties of the ASD were evaluated using pooled data from two clinical trials, ACROBAT Evolve [ 16 ] (NCT03792555; n = 13) and ACROBAT Edge [ 17 , 18 ] (NCT03789656; n = 47). ACROBAT Evolve was a phase 2, double-blind, placebo-controlled, multicenter, randomized withdrawal study to evaluate the safety, pharmacokinetics, and efficacy of paltusotine in patients with an IGF-I within the age-related reference range while on SRL therapy in the form of octreotide long-acting release (LAR) or lanreotide depot.…”
Section: Methodsmentioning
confidence: 99%
“…The recently published phase II ACROBAT Edge study provides the first data assessing the safety and efficacy of paltusotine in patients with acromegaly. 35 Patients were enrolled into the primary analysis cohort and four additional exploratory groups. The primary analysis cohort (Group 1) comprised patients who were partial responders to stable iSRL.…”
Section: Advent Of Oral Somatostatin Receptor Ligandsmentioning
confidence: 99%